Spectral measure function separability and reflectionless potentials - A. Kincanon, Eric (International Journal of Applied Mathematical Research, 2018)
Both reflectionless potentials and special conditions on the spectral measure function have been well studied in inverse scattering theory. This short paper considers a spectral measure function that is separable and shows that it is equivalent to the potential being reflectionless.
Keywords: Inverse Scattering; Reflection less Potentials.